An Analysis of Sector-Based Water Supply and Demand: Mapping the Possible Water Development and Management Ways for Sanyati Catchment, Zimbabwe - Kusena, Winmore; Debwe, Thomas (IGI Global, 2022)
This chapter sought to assess sector-based current water use levels in Sanyati catchment, assess a possibility of new ways of managing the catchment water using inter-basin transfer systems, and assess future water demands projection using WEAP model. The study was both quantitative and qualitative in nature. Interviews and observations were the main primary data collection instruments. Findings showed that the main sectors and institutions that utilised water in the catchment were mining, agriculture, manufacturing industry, and local authorities. Local authorities and farming sectors were the major users of water. WEAP model results showed a steady increase in demand for water as a result of both population growth and agricultural activities water demand. The study mapped possible inter-basin transfer routes and recommends water harvesting as part of development and management in Sanyati catchment to address the problem of water shortage.